The Level of Satisfaction of the Residents on the Public Healthcare Services in the Isolated Mountain Barangays of Cebu City: A Research as Basis for Crafting an Action Plan - Tulaytay, Donna Mae E.; Fonte, Allain D.; Basallo, Ma. Leslie B. (Advances in Social Sciences Research Journal, 2024)
This research study aims to investigate the level of satisfaction among residents of isolated mountain barangays in Cebu City regarding healthcare services. The identified barangays for this study are Bonbon, Sudlon 1, Sudlon 2, and Sinsin. By distributing survey questionnaires to randomly selected participants from each barangay, the study sought to assess residents’ satisfaction levels with respect to healthcare services provided within their respective communities. The study employed a mixed-methods approach, incorporating both quantitative and qualitative data collection techniques. The questionnaires were designed to measure various aspects of healthcare services, including accessibility, quality of care, healthcare personnel, facilities, and overall satisfaction. Data analysis involved descriptive statistics to examine the quantitative data. Qualitative data were analyzed using thematic analysis to identify recurring themes and patterns in participants’ responses. The preliminary findings of the study indicated that residents’ satisfaction levels with healthcare services in these isolated mountain barangays varied across different aspects. While some residents expressed overall satisfaction, others identified specific areas that required improvement. Accessibility, availability of healthcare personnel, quality of care, and the adequacy of healthcare facilities emerged as critical factors influencing residents’ satisfaction. The research findings have important implications for policymakers, healthcare providers, and local government units in improving healthcare services in isolated mountain barangays. The study provides valuable insights into residents’ perceptions, allowing for targeted interventions and the development of strategies to address the identified areas of concern.